2022
DOI: 10.3390/ijms23031845
|View full text |Cite
|
Sign up to set email alerts
|

The Anxiolytic Drug Buspirone Prevents Rotenone-Induced Toxicity in a Mouse Model of Parkinson’s Disease

Abstract: A pharmacological and genetic blockade of the dopamine D3 receptor (D3R) has shown to be neuroprotective in models of Parkinson’s disease (PD). The anxiolytic drug buspirone, a serotonin receptor 1A agonist, also functions as a potent D3R antagonist. To test if buspirone elicited neuroprotective activities, C57BL/6 mice were subjected to rotenone treatment (10mg/kg i.p for 21 days) to induce PD-like pathology and were co-treated with increasing dosages of buspirone (1, 3, or 10 mg/kg i.p.) to determine if the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
0
3
0
2
Order By: Relevance
“…[ 43,44 ] BSP has powerful antioxidant, anti‐inflammatory, and brain energy metabolism benefits. [ 25–28 ] Thus, this study aimed to investigate the protective role of BSP against MTX‐induced neurotoxicity. Our histopathological findings showed that BSP treatment reduced MTX‐induced neurotoxicity while increasing hippocampal cell integrity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 43,44 ] BSP has powerful antioxidant, anti‐inflammatory, and brain energy metabolism benefits. [ 25–28 ] Thus, this study aimed to investigate the protective role of BSP against MTX‐induced neurotoxicity. Our histopathological findings showed that BSP treatment reduced MTX‐induced neurotoxicity while increasing hippocampal cell integrity.…”
Section: Discussionmentioning
confidence: 99%
“…[ 22 ] BSP is linked to improved pilocarpine‐induced seizures, [ 23 ] trauma brain injury‐induced cognitive impairment and histological abrasions, [ 24 ] and rotenone‐induced Parkinson's disease. [ 25 ] Even though BSP possesses antioxidant and anti‐inflammatory effects, [ 25–28 ] its potential impact on the pathogenesis of MTX‐evoked hippocampal intoxication and associated molecular mechanisms are still unknown. As a result, the current study investigated the potential anti‐inflammatory and antioxidant effects of BSP in attenuating MTX‐induced hippocampal toxicity, as well as the molecular mechanisms underlying oxidative stress and the inflammatory response, such as the NF‐κB and ROS/NLRP3/caspase‐1 signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Буспирон же имеет модулирующее действие на D3-дофаминовые рецепторы, поэтому потенциально может оказывать нейропротекторный эффект на течение заболевания, что доказа-но на животных моделях. В исследованиях на мышах с искусственно созданной картиной БП с помощью инъекции ротенона использование буспирона в высоких дозах предотвращало дефицит моторной и исследовательской функции, защищало дофаминергические нейроны от дегенерации и уменьшало экспрессию медиаторов воспаления, одновременно повышая экспрессию нейротрофических факторов и защитных нейропептидов в некоторых областях ЦНС [39,40]. Кроме того, в исследованиях на крысах буспирон восстанавливал уровни митохондриального маркера OPA1 и антиоксидантного фермента SOD1, а также предотвращал нарушения работы двух нейропротекторных и иммуномодулирующих пептидов PACAP и VIP по всему мозгу.…”
Section: другие механизмы действия буспирона в терапии тревожных расс...unclassified
“…При этом в отдельных исследовательских работах было показано, что наравне с подавлением провоспалительных цитокинов ИЛ-1β и ИЛ-6 применение буспирона сопровождалось глобальной активацией противовоспалительного маркера Arg1, а также повышением экспрессии фактора роста нервов в уязвимых областях ЦНС, в т. ч. в области гиппокампа и миндалины, что говорит о стимуляции нейропластичности, выживании клеток и, возможно, даже росте аксонов на фоне использования препарата. Вероятно, схожие процессы происходят и в головном мозге человека, для подтверждения которых требуется проведение дополнительных исследований [40]. Сейчас можно сказать, что нейропротекторный эффект буспирона может стать дополнительным бонусом при применении его у пациентов с различными аффективными нарушениями.…”
Section: другие механизмы действия буспирона в терапии тревожных расс...unclassified
“…Studies have shown that 5-HT1A receptor activation can exert neuroprotective effects in various neuronal systems [7][8][9], and emerging evidence suggests it has relevance to the retina, particularly in contexts involving oxidative stress and neuroinflammation. Moreover, buspirone has exhibited robust antioxidant capabilities in preclinical models [10,11] aiding in the attenuation of oxidative damage, a pivotal hallmark of AMD pathogenesis [12,13].…”
Section: Introductionmentioning
confidence: 99%